Are the Accompanying Cations of Doping Anions Influential in Conducting Organic Polymers? The Case of the Popular PEDOT. Issue 63 (24th September 2019) - Fuentes, Isabel; Mostazo‐López, María José; Kelemen, Zsolt; Compañ, Vicente; Andrio, Andreu; Morallón, Emilia; Cazorla‐Amorós, Diego; Viñas, Clara; Teixidor, Francesc
Abstract: Conducting organic polymers (COPs) are made of a conjugated polymer backbone supporting a certain degree of oxidation. These positive charges are compensated by the doping anions that are introduced into the polymer synthesis along with their accompanying cations. In this work, the influence of these cations on the stoichiometry and physicochemical properties of the resulting COPs have been investigated, something that has previously been overlooked, but, as here proven, is highly relevant. As the doping anion, metallacarborane [Co(C2 B9 H11 )2 ] − was chosen, which acts as a thistle. This anion binds to the accompanying cation with a distinct strength. If the binding strength is weak, the doping anion is more prone to compensate the positive charge of the polymer, and the opposite is also true. Thus, the ability of the doping anion to compensate the positive charges of the polymer can be tuned, and this determines the stoichiometry of the polymer. As the polymer, PEDOT was studied, whereas Cs +, Na +, K +, Li +, and H + as cations. Notably, with the [Co(C2 B9 H11 )2 ] − anions, these cations are grouped into two sets, Cs + and H + in one and Na +, K +, and Li + in the second, according to the stoichiometry of the COPs: 2:1 EDOT/[Co(C2 B9 H11 )2 ] − for Cs + and H +, and 3:1 EDOT/[Co(C2 B9 H11 )2 ] − for Na +, K +, and Li + . The distinct stoichiometries are manifested in the physicochemical properties of the COPs, namely in the electrochemical response, electronic conductivity, ionic conductivity, and capacitance. Abstract : Great company ! The accompanying cations of the doping anions [Co(C2 B9 H11 )2 ] − have been proven to be non‐innocent in the conducting organic polymers (COPS) prepared with the polymer PEDOT and the metallacarborane [Co(C2 B9 H11 )2 ] − (see figure). The accompanying cations determine the stoichiometries of the COPS, and the stoichiometries in turn influence the electrochemical properties.